Pelaksanaan Program Literasi Di Sekolah Dasar Lima Puluh Kota, Kampar, Dan Rokan Hilir: - Chici Anshari; Dinda Adeliya; Icha Nuraini Mendeita; Febrina Dafit (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
The rise of the school Literacy Movement (GLS) which is being promoted by the government is currently attracting interest in conducting research on the implementation of literacy programs at SDN 03 Gunung Malintang, SDN 001 Kasikan, SDN 007 Mukti Jaya in the 2022/2023 academic year. This study aims to determine the process of developing literac programms carried out by schools and the obstacles they face. The research methodology employed in this study is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The process of assessing the credibility of the data involves employing triangulation, wherein the gathered data is subjected to analysis through data reduction, data presentation, and the formulation of conclusions. The findings indicated that the literacy program, which was executed at SDN 03 Gunung Malintang, yielded certain outcomes, SDN 001 Kasikan, SDN 007 Mukti Jaya, based on the implementation time, there are two types, namely daily and weekly. Daily literacy activities are saving, reading and writing corners, fast counting, while literacy activities weekly are library visits, collecting cash memorizing multiplication, short stories, digital-based learning media, getting to know the local culture. The obstacles to implementing the literacy program at SDN 03 Gunung Malintang, SDN 001 Kasikan, SDN 007 Mukti Jaya is connected to the provision of resources and structures that facilitate literacy initiatives, as well as addressing challenges related to teacher engagement and class dynamics.